The impact of the macroeconomic variables on the profitability of the Lima Stock Exchange - Chambi Condori, Pedro Pablo (2020)
Objective: The main objective of the research is aimed to explain the implications of macroeconomic variables on the profitability of the Lima Stock Exchange. Method: The -methodology to follow is the use of the least- squares model for the expression of a multivariate model with historical data from Peru's macroeconomic variables, such as the growth rate of GDP (CE), exchange rate (TC), interest rate (IT), inflation (IP), and the dependent variable: returns of the Lima Stock Exchange (R_IGBVL). Results: Obtained the econometric model, confirms the positive impact of GDP growth rate and exchange rate variables on the returns of the Lima Stock Exchange. Conclusions: In line with the top down fundamental analysis theory of financial markets, it evidences the positive incidence of the variables growth Peruvian economy and exchange rate on the returns of the Lima Stock Exchange, by reason of the strengthened presence of mining stocks on the Peruvian stock market. One the other hand, a negative relationship on the part of the interest rate and inflation rate variables.